Deprivation in slums and child poverty: study on Kolkata. Issue 7 (11th July 2016) - De, Indranil; Nag, Tirthankar
Abstract : Purpose: – The study attempts to look into the poverty and deprivation in slums across various social and religious groups and its bearing on the children. It not only analyses income poverty but also looks at derivation of access to basic services including water, sanitation and drainage. The purpose of this paper is to compare and contrast the income and non-income deprivation of childbearing and non-childbearing households. Design/methodology/approach: – The study is based on a survey of 541 sample households selected from 23 slums of Kolkata, India. The authors have adopted a mixture of cluster sampling and systematic sampling technique. The slums of Kolkata have been segregated into three regions and further segregated by overlaying the population and average monthly income of slums. Slums have been selected randomly from these stratums. Households have been selected from the slums by systematic sampling method. Findings: – The Muslim and backward caste households are more deprived with respect to income and access to basic services as compared to Hindu general (upper) caste. Deprivations with respect to income and basic services are more pronounced for households having child than for households not having child. Childbearing households are less likely to receive better water supply, sanitation and drainage services as compared to others due to their religious and residential identities. Slum children get affected by the complex political economy of basic service delivery. The study also finds that electoral competition has positive and political clientelism has negative impact on access to basic services. Research limitations/implications: – The study is based on results obtained from survey in one city of India. Hence, these results cannot be generalized for India or for the developing countries taken together. Further studies across cities of developing countries are required to arrive at any generalized conclusion. Practical implications: – The study suggests that public policies should attempt to disentangle minorities and children from the local political economy. Otherwise, deprivation and disparity even across low income households living in slums would persist. Deprivation of child bearing households would lead to a deteriorating future for the slum children. Social implications: – This paper have pave the path for new generation public policy for the urban poor and minorities. Originality/value: – This paper highlights the incidence of deprivation of minorities and childbearing households vis-à-vis other households in the slums. It contributes to the overall understanding on urban poverty.